Review on melanosis coli and anthraquinone-containing traditional Chinese herbs that cause melanosis coli - Zhang, Ruiyuan; Huang, Cai; Wu, Fan; Fang, Ke; Jiang, Shujun; Zhao, Yan; Chen, Guang; Dong, Ruolan (Frontiers in Pharmacology, 2023)
Backgrounds The incidence of melanosis coli (MC) has gradually increased annually, attracting significant attention and efforts into this field. A potential risk factors for MC is the long-term use of anthraquinone laxatives in patients with constipation. Most traditional cathartic drugs are made from herbs from traditional Chinese medicine (TCM) preparations containing anthraquinone compounds.Aim of the studies Aim of the study This review aims to provide guidance and rationale for the application of traditional Chinese herbs containing anthraquinones for physicians and MC research. Materials and Methods We reviewed risk factors and pathogenesis of MC, and natural anthraquinones isolated from TCM herbs. We searched PubMed and the Chinese National Knowledge Infrastructure (CNKI) databases for literature related to MC published in recent years and provide a list of herbs in TCM containing anthraquinones that could cause MC. Results Based on TCM theories and modern pharmacological research achievements, we identified 48 herbs belonging to 15 families represented by Polygonaceae, Fabaceae, Rhamnaceae, and Rubiaceae, which may play a role in the pathogenesis of MC. Of these, the herbs most commonly used include Rhei Radix et Rhizome, Radix Polygoni Multiflori, Rhizoma Polygoni Cuspidati, Semen Cassiae, Aloe and Rubiae Radix et Rhizoma. Conclusions Due to a lack of awareness of the chemical composition of TCM herbs, many patients with constipation and even some TCM physicians use cathartic herbal remedies containing a large number of anthraquinones to relieve defecation disturbances, resulting in a long-term dependence on these herbs, which is associated with most cases of MC. When such treatments are prescribed, TCM physicians should avoid long-term use in large doses to reduce their harm on colonic health. Individuals who take health-care products containing these herbs should also be under the supervision of a doctor.